Analysis Of Career Path Startup Companies PT. Sahabat Gadai - Fitra Rahmadani, Fitra (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Abstract This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. This research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to the research. The purpose of this research is to analyze how PT. Sahabat Gadai organizes and manages career paths in this dynamic startup environment. This research will identify the challenges faced in implementing a career path system, as well as evaluate its impact on employee motivation and performance. From the results of this research, it can be seen that PT Sahabat Gadai employees are more motivated by the promotion structure and of course they are driven by financial needs. This can be seen from the data results which show that 40% of the sample chose this. Because this company is a newly developing company, PT Sahabat Gadai continues to improve its self-development program.